A novel multilocus variable-number tandem repeat analysis for Bordetella parapertussis. Issue 11 (15th October 2019) - Kamachi, Kazunari; Otsuka, Nao; Fumimoto, Rei; Ozawa, Kensuke; Yao, Shu-Man; Chiang, Chuen-Sheue; Luu, Laurence Don Wai; Lan, Ruiting; Shibayama, Keigo; Watanabe, Mineo
Abstract : Purpose. Human-adapted Bordetella parapertussis is one of the causative agents of whooping cough; however, there are currently no genotyping systems with high discriminatory power for this bacterial pathogen. We therefore aimed to develop a multilocus variable-number tandem repeat analysis (MLVA) for human-adapted B. parapertussis . Methodology. Four highly polymorphic variable number tandem repeat (VNTR) loci in the B. parapertussis genome were selected and amplified by multiplex PCR. MLVA was performed based on the number of tandem repeats at VNTR loci. The discriminatory power of MLVA was evaluated with three laboratory reference strains and 50 human isolates of B. parapertussis . Results. Multiplex PCR-based MLVA characterized 53 B. parapertussis reference strains and isolates into 25 MLVA types and the Simpson diversity index was 0.91 (95 % confidence interval, 0.86–0.97). The three reference strains exhibited different MLVA types. Thirty-one Japanese isolates, ten French isolates and three Taiwanese isolates belonged to fourteen, nine and three MLVA types, respectively. In contrast, all five Australian isolates belonged to the same type. Two Japanese isolates collected from patients with known epidemiological links had the same type. Conclusion. Our novel MLVA method has high discriminatory power for genotyping human B. parapertussis . Regarding this organism, this genotyping system is a promising tool for epidemiological surveillance and investigating outbreaks.